Knowledge, attitudes and practices of health care providers trained in responding to violence against women: a pre- and post-intervention study - Sanjida Arora; Sangeeta Rege; Padma Bhate-Deosthali; Soe Soe Thwin; Avni Amin; Claudia García-Moreno; Sarah R. Meyer (BMC, 2021)
Abstract Background Violence against women is a serious public health concern, and is highly prevalent globally, including in India. Health-care providers [HCPs] can play an important role in addressing and reducing negative consequences of violence against women. We implemented a pre-post intervention study of HCP training in three tertiary care facilities in Maharashtra, India. Methods The study used a pre-post intervention design with assessment of HCPs' (n = 201) knowledge, attitudes, perceived preparedness and practice at three time points: before training, after training and at 6 months follow- up. Results Total median score of knowledge about common signs and symptoms of violence (8.89 vs, 10.00), attitudes towards acceptability of violence (9.05 vs. 10.00), individual (6.74 vs. 10.00) and system level preparedness (6.11 vs. 8.14) improved from pre to post- training. The generalized estimating equation [GEE] model, adjusted for age, sex, site and department, showed an improvement in knowledge, attitudes and preparedness post- training. The change from pre to 6 months follow- up was not significant for attitude. Conclusions This package of interventions, including training of HCPs, improved HCPs' knowledge, attitudes and practices, yet changes in attitudes and preparedness did not sustain over time. This study indicates feasibility and positive influence of a multi-component intervention to improve HCP readiness to respond to violence against women in a low-resource setting. Future phases of intervention development include adapting this intervention package for primary and secondary health facilities in this context, and future research should assess these interventions using a rigorous experimental design. Finally, these results can be used to advocate for multi-layered, systems-based approaches to strengthening health response to violence against women.